2019
DOI: 10.1055/a-0846-5726
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Unilateral and Bilateral Sacrospinous Ligament Fixation Using Minimally Invasive Anchorage

Abstract: Objective The aim of this study was to determine the effectiveness of a newly developed anchoring system for unilateral sacrospinous ligament fixation (USSLF) and bilateral sacrospinous ligament fixation (BSSLF) procedures. Material and Methods Ninety-three patients with pelvic prolapse who were treated surgically with the Anchorsure System® between 2013 and 2018 were included in the study. USSLF was performed in 52 patients (group 1), and BSSLF was performed in 41 patients (group 2). Pelvic organ pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…The study of Salman et al (19) reported that no rectal injury occurred intraoperatively, which is consistent with our results. The data regarding functional outcome for the bowel (CRADI-8 scores) after h-SSLF and LSC showed hardly any improvement for most patients.…”
Section: Discussionsupporting
confidence: 93%
“…The study of Salman et al (19) reported that no rectal injury occurred intraoperatively, which is consistent with our results. The data regarding functional outcome for the bowel (CRADI-8 scores) after h-SSLF and LSC showed hardly any improvement for most patients.…”
Section: Discussionsupporting
confidence: 93%
“…In our series, 81.1% of the SSLF were performed bilaterally. Our results are comparable to Salman’s study, which compared unilateral versus bilateral SSLF, reporting recurrence of vaginal vault prolapse in two patients (3.84%) in the unilateral group and no recurrences for the bilateral group, with no statistically significant differences between the two groups with a follow-up of 6 months after surgery [ 21 ].…”
Section: Discussionsupporting
confidence: 86%
“…Mehmet Baki et al [45] demonstrated that bilateral SSLF with mesh allowed to establish adequate pelvic support for genital prolapse and suggested that the vaginal axis may be closer to the original anatomical position. In contrast, Salman et al [46] proved that unilateral and bilateral SSLF techniques are associated with similar clinical outcomes. In a recently published meta-analysis involving 4120 patients after SSLF and SCP, SSLF was associated with lower success rate (88.32% vs. 91.45%), higher recurrence (11.58% vs. 8.32%) and dyspareunia (14.36% vs. 4.67%) rates, shorter operative time, lower hemorrhage and wound infection rate and lower and fewer gastrointestinal complications [42].…”
Section: Discussionmentioning
confidence: 93%